Big Data : análise e a avaliação de ferramentas para gerenciamento de grande volume de dados - Gehring, Cristiano (2018)
This article presents the analysis of the Big Data concept and the evaluation of the tools that work with large volume data management. The work was developed with the creation of two clusters in distinct environments, being they Amazon Web Service and Google Cloud Platform, installed in the platform Hadoop with use of tool Hive. The practical tests were carried out from a meteorological database of the Centro de Previsão de Tempo e Estudos Climáticos / Instituto Nacional de Pesquisas Espaciais. At the end of the work, with the completion of the tests, the Amazon Web Service cluster performed better.